2013
DOI: 10.7763/joebm.2013.v1.71
|View full text |Cite
|
Sign up to set email alerts
|

Personal Medical Information Management: The Information Privacy Culture of Asian Countries

Abstract: Abstract-Asian communities have a distinctive concept in perceiving the value of information privacy, which is completely unique from the description set by western countries. This paper gathers the definition and the theory of information privacy culture. Based on the culture dimension theory of Hofstede, it attempts to reveal the perception and concern of Asian countries towards the privacy of its personal information. A survey was conducted in one of the public universities in Malaysia in order to gauge the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 22 publications
(19 reference statements)
0
6
0
Order By: Relevance
“…Miltgen & Peyrat-Guillard, 2014;Jensen & Wagner, 2018); or used data from a single country to generalize about culture's impacts on privacy within a given geographic region (e.g. Samsuri & Ismail (2013); and, Mohammed & Tejay (2017)); or limited themselves to comparing countries across two different geographic or cultural regions (e.g., Thomson et al, 2015 andLowry et al, 2011, among others). That collection of studies provides us with, at best, a fragmented global perspective of the influence of culture on privacy and provide little evidence of the role of regulatory structure within that global perspective of privacy.…”
Section: Discussionmentioning
confidence: 99%
“…Miltgen & Peyrat-Guillard, 2014;Jensen & Wagner, 2018); or used data from a single country to generalize about culture's impacts on privacy within a given geographic region (e.g. Samsuri & Ismail (2013); and, Mohammed & Tejay (2017)); or limited themselves to comparing countries across two different geographic or cultural regions (e.g., Thomson et al, 2015 andLowry et al, 2011, among others). That collection of studies provides us with, at best, a fragmented global perspective of the influence of culture on privacy and provide little evidence of the role of regulatory structure within that global perspective of privacy.…”
Section: Discussionmentioning
confidence: 99%
“…This subject has become a popular topic and is widely debated in recent years. Triggered by the rapid technological advancement, the government and private sector actively gathered the public's information and this rising concern on the safety of their data [1].…”
Section: Introductionmentioning
confidence: 99%
“…Although societies value some form of privacy, there are significant differences in the concept of confidentiality across cultures. Culture could influence the concept of privacy as to when protection is needed and the level of its importance [1].…”
Section: Introductionmentioning
confidence: 99%
“…Many business researchers have studied the impact of culture on ethical decision making (Bellman et al, 2004;Capurro, 2006;Chen et al, 2013;Chung et al, 2008;Guillen et al, 2002;Hui et al, 2007;Lowry et al, 2014;Mele et al, 2006;Moores, 2008;Nakada and Tamura, 2005;Wood et al, 2004). Some of these studies found that culture impacted people's attitudes and behaviors in relation to software piracy (Lowry et al, 2014;Moores, 2008), privacy concerns (Bellman et al, 2004;Chen et al, 2013;Nakada and Tamura, 2005;Samsuri and Ismail, 2013), and data access (Lowry et al, 2014).…”
Section: Introductionmentioning
confidence: 99%